Electrode for zinc-bromine flow battery as well as preparation and application of electrode
By using the core-shell homogeneous carbon nanosphere material prepared by domain-limited pyrolysis as electrodes in zinc bromine flow batteries, the problems of Br2 diffusion and zinc dendrites are solved, and the catalytic activity, cycle stability and life of the battery are significantly improved.
Patent Information
- Application Number
- CN202311268481.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
The strong volatility and diffusion of Br2 in zinc-brominated flow batteries lead to environmental safety problems, the reduction of active substances, migration to the negative electrode leads to self-discharge of the battery, reducing the capacity, efficiency and service life of the battery; there are uncontrollable side reactions in the negative electrode of zinc, such as dendrites, which limit the cycle life of the battery.
Core-shell homogeneous carbon nanosphere materials with cavity structures were prepared by using solid polymer spheres synthesized without surfactant as the core and dense silica as the clad layer to construct the core-shell structure and then perform domain-limited pyrolysis. They were used as the positive and negative electrode materials of zinc bromine flow batteries to improve catalytic activity, inhibit bromine diffusion and the formation of zinc dendrites.
It significantly improves the catalytic activity of the bromine pair, inhibits the diffusion of bromine, slows down capacity attenuation, extends the battery life and cycle stability, and improves the battery power density and cycle life.
Smart Images

Figure CN119725588A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of liquid flow battery electrodes, in particular to the field of zinc-bromine liquid flow battery electrode preparation and application. Background Art
[0002] Renewable energy generation such as wind and solar energy has great instability and discontinuity, which will cause impact on the power grid in practical applications. It is necessary to introduce energy storage systems for large-scale grid connection of renewable energy. New energy storage has a short construction period, simple and flexible site selection, strong adjustment capacity, better matching with the development and consumption of new energy, and its advantages are gradually becoming prominent. It is imperative to accelerate the large-scale application of advanced energy storage technology. Among them, liquid flow battery technology has been widely studied in the field of large-scale energy storage technology due to its advantages such as independent design of output power and energy storage capacity, high energy efficiency, safety and reliability. The zinc-bromine liquid flow battery has abundant sources of active materials, low cost and high energy density, which makes it valued in the field of user-side energy storage. However, there are still some urgent problems to be solved for the further commercialization and industrialization of zinc-bromine liquid flow batteries: 1) Br2 has strong volatility and diffusivity, which causes environmental safety, reduction of active materials, migration to the negative electrode leading to battery self-discharge and other problems, reducing the capacity, efficiency and service life of the battery; 2) There are uncontrollable side reactions such as dendrite growth in the zinc negative electrode, which limits the cycle life of the battery. At present, the commonly used solutions for bromine positive electrodes are as follows: 1) by adding complexing agents to the electrolyte, the concentration of free bromine is reduced to reduce the volatilization and diffusion of bromine; 2) modifying the diaphragm material to reduce the penetration of bromine through the pore size screening effect; 3) modifying the electrode to improve its catalytic activity. The solutions for zinc negative electrodes are: 1) adding electrolyte additives to regulate the zinc deposition process to help form a uniform layered / blocky zinc morphology; 2) modifying the electrode surface or designing a specific electrode structure to optimize the current distribution on the electrode surface and the flow rate distribution of the electrolyte, thereby adjusting the zinc deposition morphology; 3) regulating the structure and surface properties of the ion conduction membrane to achieve effective regulation of the zinc deposition morphology of the zinc negative electrode. However, the addition of electrolyte additives will reduce the conductivity and mass transfer rate of the electrolyte; the diaphragm is expensive and has high resistance. After modification, the membrane resistance increases, which is not conducive to the electrochemical reaction of the bromine electrode, resulting in increased battery polarization and decreased performance. Summary of the invention
[0003] In order to solve the above technical problems, the present invention aims to invent a multifunctional electrode for use in zinc-bromine flow batteries that has the functions of improving the catalytic activity of the bromine positive electrode, alleviating the diffusion of bromine, and inhibiting the effect of zinc dendrites. A core-shell homogeneous carbon nanosphere material with a cavity structure is prepared by using a solid polymer ball synthesized without surfactant as the core and dense silica as the coating layer to construct a core-shell structure and then perform confined pyrolysis. When used as a positive electrode material for zinc-bromine flow batteries, due to its large specific surface area and excellent adsorption capacity, it can significantly improve the catalytic activity of the bromine electrode pair. At the same time, with the help of the strong adsorption effect of the carbon core and the carbon shell and the size effect of the spherical structure, bromine can be captured in the core-shell homogeneous carbon nanosphere structure, which can effectively inhibit bromine diffusion and slow down capacity decay. When used as a negative electrode material for zinc-bromine flow batteries, the cavity structure and the space between the carbon nanospheres can provide more zinc deposition sites and accommodate more zinc deposition, thereby inhibiting the formation of zinc dendrites and improving the battery life and cycle stability.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0005] On the one hand, the present invention provides an electrode for a zinc-bromine flow battery, wherein the electrode uses a conductive current collector as a matrix, and supports a core-shell homogeneous carbon nanosphere material with a cavity structure on the matrix, wherein the core size is 100-400nm, the shell wall thickness is 10-50nm, and the pore size is 1-50nm.
[0006] Based on the above scheme, preferably, the core size of the core-shell homogeneous carbon nanosphere material with a cavity structure is 200-300 nm, the shell wall thickness is 20-40 nm, and the pore size is 1-30 nm.
[0007] Based on the above scheme, preferably, the loading amount of the core-shell homogeneous carbon nanosphere material with a cavity structure on the substrate is 1-15 mg / cm 2 , more preferably 5-12 mg / cm 2 .
[0008] Based on the above solution, preferably, the substrate is carbon felt, graphite felt or carbon cloth.
[0009] In another aspect, the present invention provides a method for preparing the above electrode, comprising the following steps:
[0010] 1) Weigh a certain amount of resorcinol and formaldehyde and dissolve them in 100 mL of deionized water under stirring (the molar ratio is constant at 1:2-1:4). Then, add 0.5-1 mmol of 1,6-hexanediamine to the above solution, react for 30 minutes, then add 50-100 μL of ammonia water (mass fraction 25%), and react at 80°C for 3-6 hours. After cooling, centrifugation, washing with water, and drying, solid polymer spheres are obtained;
[0011] 2) Take 100-400 mg of the solid polymer spheres and disperse them in deionized water, add 1.0 mL of ammonia water and 24 mL of anhydrous ethanol, add 10-50 mL of a pre-dissolved CTAB aqueous solution after ultrasonic dispersion, stir for 30 min, add 1-5 mL of TEOS, react for 10-20 h, centrifuge, wash with deionized water until neutral, and dry to obtain a core-shell structure polymer @ silicon oxide material;
[0012] 3) subjecting the core-shell structure polymer @ silicon oxide material to high temperature pyrolysis carbonization to obtain core-shell carbon @ silicon oxide material, wherein the high temperature pyrolysis carbonization conditions are as follows: the temperature of the first stage is 150-350°C, the time is 1-5h, the heating rate is 1-10°C / min, and the temperature of the second stage is 500-900°C, the time is 1-5h, the heating rate is 1-10°C / min, and an inert atmosphere is used;
[0013] 4) Dispersing the core-shell carbon@silicon oxide material in a 2M sodium hydroxide solution (volume ratio of alcohol to water is 1:3), reacting at 50-80° C. for 20-36 hours, centrifuging, washing with water until neutral, and drying to obtain the core-shell homogeneous carbon nanosphere material with a cavity structure;
[0014] 5) Loading the core-shell homogeneous carbon nanosphere material with a cavity structure on a conductive current collector substrate: adding the core-shell homogeneous carbon nanosphere material with a cavity structure into isopropanol, wherein the mass ratio of isopropanol to the core-shell homogeneous carbon nanosphere material with a cavity structure is 25-100; adding a binder, such as one of Nafion, PVDF or PTFE, wherein the mass ratio of the binder to the core-shell homogeneous carbon nanosphere material with a cavity structure is 2-8, and spraying the resultant on a conductive current collector substrate after ultrasonic dispersion.
[0015] Based on the above scheme, preferably, in step 1), the molar ratio of resorcinol to formaldehyde is constant at 1:2-1:3, the amount of 1,6-hexanediamine is 0.5-0.8 mmol, the amount of ammonia water is 50-80 μL (mass fraction 25%), and the reaction time is 2-5 h.
[0016] Based on the above scheme, preferably, in step 2), the amount of the CTAB aqueous solution is 10-30 mL, the amount of TEOS is 1-3 mL, and the reaction time is 15-20 h.
[0017] Based on the above scheme, preferably, in step 3), the temperature of the first stage is 150-300°C, the time is 1-3h, the heating rate is 5-10°C / min, and the temperature of the second stage is 500-700°C, the time is 1-3h, the heating rate is 5-10°C / min, and an inert atmosphere is used.
[0018] Based on the above scheme, preferably, in step 4), the alkaline solution used for etching silicon oxide is composed of 2M sodium hydroxide solution (alcohol-water volume ratio 1:3), and the etching conditions are 50-60° C. for reaction for 24-32 hours.
[0019] Based on the above scheme, preferably, in step 5), the mass ratio of isopropanol to the core-shell homogeneous carbon nanosphere material with a cavity structure is 25-100, preferably 40-80; the binder is Nafion, PVDF or PTFE, preferably Nafion, and the mass ratio of the binder to the core-shell homogeneous carbon nanosphere material with a cavity structure is 2-8, preferably 3-5.
[0020] The electrode of the present invention has the advantages of low preparation cost, high bromine catalytic activity, strong bromine fixation ability, good chemical stability, and the ability to control the zinc dendrite morphology. The prepared electrode inhibits the migration and diffusion of bromine, reduces the self-discharge reaction of the battery, and inhibits the generation of zinc dendrites, effectively improving the capacity retention rate and cycle stability of the zinc-bromine liquid flow battery, and greatly improving the battery power density and cycle life.
[0021] Beneficial effects of the present invention:
[0022] (1) The electrode prepared by the present invention has a core-shell homogeneous carbon nanosphere material with a cavity structure, which can promote the adsorption of bromine. At the same time, with the help of the adsorption effect of the core and shell wall and the size effect of the spherical structure, bromine and polybromine can be confined in the core-shell homogeneous carbon nanosphere with a cavity structure. When used as a positive electrode material in a zinc-bromine liquid flow battery, it can significantly inhibit the diffusion of bromine and slow down the capacity decay, thereby improving the battery efficiency; when used as a negative electrode material, its cavity structure and the space between the carbon nanospheres can provide more zinc deposition sites and accommodate more zinc deposition, making the zinc deposition more uniform and dense, thereby inhibiting the formation of zinc dendrites and improving the battery life and cycle stability.
[0023] (2) The electrode prepared by the present invention has multiple functions: high catalytic activity, excellent bromine fixation ability, and regulation of zinc dendrites. It can be used in positive and negative electrodes at the same time, reducing the complexity of the design of positive and negative electrodes, greatly improving the battery performance and cycle stability of zinc-bromine liquid flow batteries, and reducing costs.
[0025] (3) The process of the present invention is simple, easy to operate, low in cost, safe and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 These are SEM images of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, Comparative Example 6, Example 3, and Example 4.
[0027] Figure 2 These are TEM images of Comparative Example 2, Comparative Example 4, Comparative Example 5, Comparative Example 6, Example 3, and Example 4.
[0028] Figure 3 This is the pore size distribution diagram of Comparative Example 2, Comparative Example 4, Comparative Example 5, Comparative Example 6, Example 1, Example 2, Example 3, and Example 4.
[0029] Figure 4 It is a porosity comparison chart of Comparative Example 2, Comparative Example 6, Example 1, Example 2, Example 3, and Example 4.
[0030] Figure 5 It is a comparison chart of the specific surface areas of Comparative Example 2, Comparative Example 4, Comparative Example 5, Comparative Example 6, Example 1, Example 2, Example 3, and Example 4.
[0031] Figure 6 The cyclic voltammetry (CV) curves of Comparative Example 8, Comparative Example 9, Comparative Example 10, Comparative Example 12, Example 5, Example 6, Example 7, and Example 8 are shown.
[0032] Figure 7 It is a comparison chart of the bromine-fixing capacity of Comparative Example 13, Comparative Example 2, Comparative Example 4, Comparative Example 6, Example 1, Example 2, and Example 4.
[0033] Figure 8 These are the self-discharge performance diagrams of Comparative Example 8, Comparative Example 9, Comparative Example 10, Comparative Example 12, Example 5, Example 6, Example 7, and Example 8.
[0034] Fig. 9 These are zinc deposition morphologies of Comparative Example 8, Comparative Example 9, Comparative Example 10, Example 5, Example 6, and Example 7.
[0035] Fig.10 These are the battery performance graphs of Comparative Example 8, Comparative Example 9, Comparative Example 10, Comparative Example 12, Example 5, Example 6, and Example 7.
[0036] Fig.11 These are the battery performance diagrams of Comparative Example 8, Comparative Example 9, Example 5, and Example 8. DETAILED DESCRIPTION
[0037] The following examples are provided to further illustrate the present invention, but are not intended to limit the scope of the present invention.
[0038] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0039] In the examples of the present application, a scanning electron microscope (JSM-7800F and SUI510) was used to perform SEM tests on the materials obtained in the comparative examples and the examples.
[0040] In the examples of the present application, a transmission electron microscope (JEM-2100) was used to perform TEM tests on the materials obtained in the comparative examples and the examples.
[0041] In the examples of the present application, a gas adsorption analyzer (ASAP2010 / ASAP2010M) was used to perform N2 adsorption / desorption measurements to study the specific surface area and pore size distribution of the material. The specific surface area was calculated using the Bruauer-Emmet-Teller (BET) method.
[0042] In the examples of the present application, the materials obtained in the comparative examples and examples were tested for CV and bromine fixation ability using an electrochemical workstation Gamry multi-channel system (Gamry Interface 1000, Gamry Interface 3000).
[0043]
[0044]
[0045] Comparative Example 1:
[0046] Weigh 2mmol of resorcinol and 4mmol of formaldehyde and dissolve them in 100mL of deionized water under stirring. Add 0.5mmol of 1,6-hexanediamine to the above solution, react for 30min, then add 50μL of 25% ammonia water, and react at 80℃ for 4h. Cool to room temperature, centrifuge, wash the solid with water, and dry to obtain solid polymer spheres with a particle size of about 380nm.
[0047] Comparative Example 2:
[0048] Take 2.0g of the product prepared in Comparative Example 1 and spread it flat in a corundum boat, place it in a tubular furnace, and carry out high-temperature carbonization in Ar at a temperature of 700°C for 2h. The heating rate from room temperature to the carbonization temperature is 5°C / min. The particle size of the product of Comparative Example 2 is about 296nm.
[0049] Bromine fixation ability test:
[0050] Pretreatment of rotating ring disk electrode: polish a rotating ring disk electrode (ring is Pt, disk is glassy carbon) with a diameter of 6 mm (disk) with 30-50 nm Al2O3 polishing powder until the surface is smooth and free of marks, rinse repeatedly with deionized water, and dry for use. Take 2.5 mg of the material prepared in Comparative Example 2, mix it with 0.4 g of isopropanol and 10 μL of 0.05 wt.% Nafion solution by ultrasonic mixing to form a uniform slurry. Use a microinjector to draw 10 μL of the above slurry and transfer it to the glassy carbon electrode and evenly distribute it on the upper surface. After the solvent evaporates completely, a thin film electrode with a smooth surface is obtained as the test.
[0051] Bromine fixation ability test device and conditions: The bromine fixation performance of the material was evaluated using rotating ring disk electrode technology, and an electrochemical workstation (Gamry Multichannel System installation, Reference 3000 and Reference 1000) was used to control the voltage and current of the test system. The test conditions are as follows: the working electrode is the above-mentioned rotating ring disk electrode, the reference electrode is an Ag / AgCl electrode, the counter electrode is a graphite plate, the rotation speed of the ring disk electrode is 2000rpm, and the electrolyte composition is 2MZnBr2+3MKCl+0.4M MEPBr (N,N-methylethylpyrrolidine bromide). The oxidation current on the glassy carbon disk electrode is 1mA for 60s, and the reduction potential on the Pt ring is maintained at 0.5V vs.Ag / AgCl.
[0052] Comparative Example 3:
[0053] 400 mg of the product prepared in Comparative Example 1 was dispersed in 100 mL of deionized water, 1.0 mL of 25% ammonia water and 24 mL of anhydrous ethanol were added thereto, 10 mL of a pre-dissolved CTAB aqueous solution (15 mmol CTAB was added to 100 mL of water to prepare an aqueous solution) was added after ultrasonic dispersion, 1 mL of TEOS was added after stirring for 30 min, and the reaction was centrifuged after 16 h, washed with deionized water until neutral, and dried to obtain a core-shell structure polymer @ silicon oxide material, wherein the core diameter was 518 nm, there was no cavity, the shell wall thickness was about 138 nm, and the shell wall had no obvious pore size distribution.
[0054] Comparative Example 4:
[0055] Take 400mg of the product prepared in Comparative Example 1 and disperse it in 100mL deionized water, add 1.0mL of 25% ammonia water and 24mL of anhydrous ethanol, stir for 30min, add 1mL of TEOS, react for 16h, centrifuge, wash the solid with deionized water until neutral, and dry for use. Take 2.0g of the obtained material and spread it in a corundum boat, place it in a tube furnace, and carry out high-temperature carbonization in Ar, first keep it at 150℃ for 2h, then heat it to 700℃ and continue to keep it for 2h, with a heating rate of 5℃ / min. The product after high-temperature carbonization is dispersed in 2M sodium hydroxide solution (solvent: alcohol water volume ratio 1:3), react at 50℃ for 24h, centrifuge, wash the solid with water until neutral, and dry. Since CTAB was not added during the preparation process, no core-shell structure appeared in Comparative Example 4, and the diameter of the solid sphere was about 310nm.
[0056] Bromine fixation ability test: The pretreatment process of the rotating ring disk electrode with a diameter of 6 mm is the same as the pretreatment of the rotating ring disk electrode in Comparative Example 2, except that 2.5 mg of the material prepared in Comparative Example 4 is taken and ultrasonically mixed with 0.4 g of isopropanol and 10 μL of 0.05 wt.% Nafion solution to form a uniform slurry. Use a microinjector to draw 10 μL of the above slurry and transfer it to the glassy carbon electrode. After the solvent evaporates completely, a thin film electrode with a smooth surface is obtained as the test. The bromine fixation ability test device and conditions are the same as those in Comparative Example 2, except that only the above-treated ring disk electrode is used as the working electrode.
[0057] Comparative Example 5:
[0058] Take 400mg of the product prepared in Comparative Example 1 and disperse it in 100mL deionized water, add 1.0mL of 25% ammonia water and 24mL of anhydrous ethanol, add 10mL of pre-dissolved CTAB aqueous solution (15mmolCTAB is added to 100mL water to make an aqueous solution) after ultrasonic dispersion, stir for 30min and add 1mL TEOS, react for 8h, centrifuge, wash the solid with deionized water to neutrality, and dry for use. Take 2.0g of the obtained material and spread it in a corundum boat, place it in a tube furnace, and carry out high-temperature carbonization in Ar, first keep it at 150℃ for 2h, then heat it to 700℃ and continue to keep it for 2h, and the heating rate is 5℃ / min. The product after high-temperature carbonization is dispersed in 2M sodium hydroxide solution (solvent: alcohol water volume ratio 1:3), react at 50℃ for 24h, centrifuge, wash the solid with water to neutrality, and dry. Since the coating time was short during the preparation process, the shell layer was not successfully coated, and no core-shell structure appeared in Comparative Example 5. The diameter of the solid sphere was about 300 nm.
[0059] Comparative Example 6:
[0060] Take 400mg of the product prepared in Comparative Example 1 and disperse it in 100mL deionized water, add 1.0mL of 25% ammonia water and 24mL of anhydrous ethanol, add 10mL of pre-dissolved CTAB aqueous solution (15mmolCTAB is added to 100mL water to make an aqueous solution) after ultrasonic dispersion, stir for 30min and add 1mL TEOS, react for 16h and centrifuge, wash the solid with deionized water to neutrality, and dry for use. Take 2.0g of the obtained material and spread it in a corundum boat, place it in a tube furnace, and carry out high-temperature carbonization in Ar, heat it to 700℃ and keep it for 2h, and the heating rate is 5℃ / min. The product after high-temperature carbonization is dispersed in 2M sodium hydroxide solution (solvent: alcohol water volume ratio 1:3), react at 50℃ for 24h, centrifuge, wash the solid with water to neutrality, and dry it. Since the preparation process did not go through the two stages of low-temperature and high-temperature carbonization, the core-shell structure was not successfully prepared, and the diameter of the solid sphere of Comparative Example 6 was about 297nm.
[0061] Bromine fixation ability test: The pretreatment process of the rotating ring disk electrode with a diameter of 6 mm is the same as the pretreatment of the rotating ring disk electrode in Comparative Example 2, except that 2.5 mg of the material prepared in Comparative Example 6 is taken and ultrasonically mixed with 0.4 g of isopropanol and 10 μL of 0.05 wt.% Nafion solution to form a uniform slurry. Use a microinjector to transfer 10 μL of the above slurry to the glassy carbon electrode. After the solvent evaporates completely, a thin film electrode with a smooth surface is obtained as the test. The bromine fixation ability test device and conditions are the same as those in Comparative Example 2, except that only the ring disk electrode after the above treatment is used as the working electrode. Comparative Example 7:
[0062] Take 400 mg of the product prepared in Comparative Example 1 and disperse it in 100 mL of deionized water, add 1.0 mL of 25% ammonia water and 24 mL of anhydrous ethanol, stir for 30 min, add 1 mL of TEOS, react for 16 h, centrifuge, wash the solid with deionized water until neutral, and dry to obtain a core-shell structure polymer @ silicon oxide material. Take 2.0 g of the obtained material and spread it in a corundum boat, place it in a tube furnace, and perform high-temperature carbonization in Ar, first keep it at 50 ° C for 2 h, then heat it to 500 ° C and continue to keep it for 2 h, with a heating rate of 5 ° C / min. The product after high-temperature carbonization is dispersed in 2M sodium hydroxide solution (solvent: alcohol water volume ratio 1: 3), react at 50 ° C for 24 h, centrifuge, wash the solid with water until neutral, and dry.
[0063] Comparative Example 8:
[0064] Commercial original carbon felt, size is 3cm*3cm*5mm.
[0065] Electrochemical performance test (CV): The original carbon felt was cut into a circular shape with a diameter of 6 mm and a thickness of 2 mm. The electrochemical activity of the material was evaluated using a three-electrode system with the help of an electrochemical workstation (Gamry Multichannel System installation, Reference 3000). The test conditions were as follows: the working electrode was the original carbon felt, the reference electrode was an Ag / AgCl electrode, the counter electrode was a graphite plate, the electrolyte was 2M ZnBr2+3M KCl+0.4M MEPBr, the three electrodes were all placed in the electrolyte, and the scan rate was 10mV / s.
[0066] Self-discharge performance test: zinc-bromine flow battery was assembled, with untreated original carbon felt electrodes used for both positive and negative electrodes, commercial Daramic porous membrane as separator, and electrolyte of 2M ZnBr2+3M KCl+0.4MMEPBr at a current density of 80mA cm -2 The battery was charged and discharged 15 times under the same conditions, and then the coulombic efficiency of the 16th cycle was tested after standing for 24 hours.
[0067] The current density is 80 mA cm -2 , with a surface capacity of 40 mAh cm -2 Characterization of zinc deposition morphology under the following conditions: Assemble zinc-bromine flow batteries, use original carbon felt electrodes for both positive and negative electrodes, and use the same separator and electrolyte as above. After disassembling the cycled battery, collect the carbon felt, rinse the surface with deionized water to remove the surface electrolyte, and freeze-dry to obtain the sample to be tested by electron microscopy. Scanning electron microscopy (SEM) was used to characterize the morphology of zinc metal (dendrites) deposited on the carbon felt after charge and discharge cycles.
[0068] The current density is 80 mA cm -2 The battery performance test was carried out under the following conditions: a zinc-bromine flow battery was assembled, the positive and negative electrodes used original carbon felt electrodes, the separator was a commercial Daramic porous membrane, and the electrolyte was 2MZnBr2+3M KCl+0.4M MEPBr.
[0069] The current density is 180 mA cm -2 The battery long cycle performance test was carried out under the following conditions: a zinc-bromine flow battery was assembled, the positive and negative electrodes used original carbon felt electrodes, the diaphragm was a commercial Daramic porous membrane, and the electrolyte was 2M ZnBr2+3M KCl+0.4MMEPBr.
[0070] Comparative Example 9:
[0071] After thorough grinding, 0.05 g of the material prepared in Comparative Example 2 was weighed and mixed evenly with 0.2 g of 0.05 wt % Nafion solution and 3 g of isopropanol, and then sprayed on an original carbon felt with a size of 3 cm*3 cm*5 mm under ultrasonication for several hours.
[0072] Electrochemical performance test (CV): The working electrode was the carbon felt prepared as described above, and the test apparatus and conditions were the same as those in Comparative Example 8.
[0073] Self-discharge performance test: Assemble the zinc-bromine flow battery, use the carbon felt electrode prepared and treated as above for the positive electrode, and use the untreated original carbon felt electrode for the negative electrode, and other conditions are the same as those in the above comparative example 8. The side of the sprayed material faces the diaphragm;
[0074] The current density is 80 mA cm -2 , with a surface capacity of 40 mAh cm -2 The zinc deposition morphology was characterized under the following conditions: a zinc-bromine flow battery was assembled, the carbon felt electrode prepared and treated as above was used for the negative electrode, and the untreated original carbon felt electrode was used for the positive electrode. Other conditions and operations were the same as those in Comparative Example 8.
[0075] The current density is 180 mA cm -2The battery long cycle performance test was carried out under the following conditions: the positive and negative electrodes used the carbon felt electrodes prepared and treated as above, and the other conditions were the same as those in the above comparative example 8.
[0076] Comparative Example 10:
[0077] After thorough grinding, 0.05 g of the material prepared in Comparative Example 4 was weighed and mixed evenly with 0.2 g of 0.05 wt % Nafion solution and 3 g of isopropanol, and then sprayed on an original carbon felt with a size of 3 cm*3 cm*5 mm under ultrasonication for several hours.
[0078] Electrochemical performance test (CV): The working electrode was the carbon felt prepared as described above, and the test apparatus and conditions were the same as those in Comparative Example 8.
[0079] Self-discharge performance test: Assemble the zinc-bromine flow battery, use the carbon felt electrode prepared and treated as above for the positive electrode, and use the untreated original carbon felt electrode for the negative electrode, and other conditions are the same as those in the above comparative example 8. The side of the sprayed material faces the diaphragm;
[0080] The current density is 80 mA cm -2 , with a surface capacity of 40 mAh cm -2 The zinc deposition morphology was characterized under the following conditions: a zinc-bromine flow battery was assembled, the carbon felt electrode prepared and treated as above was used for the negative electrode, and the untreated original carbon felt electrode was used for the positive electrode. Other conditions and operations were the same as those in Comparative Example 8.
[0081] The current density is 80 mA cm -2 The battery performance test was carried out under the following conditions: a zinc-bromine flow battery was assembled, and the carbon felt electrodes prepared and treated as above were used for the positive and negative electrodes, and other conditions were the same as those in the above comparative example 8.
[0082] Comparative Example 11:
[0083] After thorough grinding, 0.05 g of the material prepared in Comparative Example 5 was weighed and mixed evenly with 0.2 g of 0.05 wt % Nafion solution and 3 g of isopropanol, and then sprayed on an original carbon felt with a size of 3 cm*3 cm*5 mm under ultrasonication for several hours.
[0084] Electrochemical performance test (CV): The working electrode was the carbon felt prepared as described above, and the test apparatus and conditions were the same as those in Comparative Example 8.
[0085] Self-discharge performance test: Assemble the zinc-bromine flow battery, use the carbon felt electrode prepared and treated as above for the positive electrode, and use the untreated original carbon felt electrode for the negative electrode, and other conditions are the same as those in the above comparative example 8. The side of the sprayed material faces the diaphragm;
[0086] The current density is 80 mA cm -2 , with a surface capacity of 40 mAh cm -2The zinc deposition morphology was characterized under the following conditions: a zinc-bromine flow battery was assembled, the carbon felt electrode prepared and treated as above was used for the negative electrode, and the untreated original carbon felt electrode was used for the positive electrode. Other conditions and operations were the same as those in Comparative Example 8.
[0087] The current density is 80 mA cm -2 The battery performance test was carried out under the following conditions: a zinc-bromine flow battery was assembled, and the carbon felt electrodes prepared and treated as above were used for the positive and negative electrodes, and other conditions were the same as those in the above comparative example 8.
[0088] Comparative Example 12:
[0089] After thorough grinding, 0.05 g of the material prepared in Comparative Example 6 was weighed and mixed evenly with 0.2 g of 0.05 wt % Nafion solution and 3 g of isopropanol, and then sprayed on an original carbon felt with a size of 3 cm*3 cm*5 mm under ultrasonication for several hours.
[0090] Electrochemical performance test (CV): The working electrode was the carbon felt prepared as described above, and the test apparatus and conditions were the same as those in Comparative Example 8.
[0091] Self-discharge performance test: Assemble the zinc-bromine flow battery, use the carbon felt electrode prepared and treated as above for the positive electrode, and use the untreated original carbon felt electrode for the negative electrode, and other conditions are the same as those in the above comparative example 8. The side of the sprayed material faces the diaphragm;
[0092] The current density is 80 mA cm -2 , with a surface capacity of 40 mAh cm -2 The zinc deposition morphology was characterized under the following conditions: a zinc-bromine flow battery was assembled, the carbon felt electrode prepared and treated as above was used for the negative electrode, and the untreated original carbon felt electrode was used for the positive electrode. Other conditions and operations were the same as those in Comparative Example 8.
[0093] The current density is 80 mA cm -2 The battery performance test was carried out under the following conditions: a zinc-bromine flow battery was assembled, and the carbon felt electrodes prepared and treated as above were used for the positive and negative electrodes, and other conditions were the same as those in the above comparative example 8.
[0094] Comparative Example 13:
[0095] Use 30-50nm Al2O3 polishing powder to polish a 6mm diameter rotating ring-disk electrode (ring is Pt, disk is glassy carbon) until the surface is smooth and free of marks, rinse repeatedly with deionized water, and dry for later use.
[0096] The bromine fixation capacity test device and conditions are the same as those of Comparative Example 2, except that only the ring disk electrode treated as above is used as the working electrode.
[0097] Embodiment 1:
[0098] Weigh 2mmol of resorcinol and 4mmol of formaldehyde and dissolve them in 100mL of deionized water under stirring. Add 0.5mmol of 1,6-hexanediamine to the above solution, react for 30min, add 50μL of 25% ammonia water, and react at 80℃ for 4h. Cool to room temperature, centrifuge, wash the solid with water, and dry to obtain solid polymer spheres. Take 400mg of the prepared solid polymer spheres and disperse them in 100mL of deionized water, add 1.0mL of 25% ammonia water and 24mL of anhydrous ethanol, add 10mL of pre-dissolved CTAB aqueous solution (15mmol CTAB is added to 100mL of water to make an aqueous solution) after ultrasonic dispersion, stir for 30min, add 1mL of TEOS, react for 16h, centrifuge, wash the solid with deionized water until neutral, and dry for use.
[0099] Take 2.0g of the material obtained in the previous step and lay it in a corundum boat, place it in a tube furnace, and carry out high-temperature carbonization in Ar, first keep it at 150°C for 2h, then heat it to 700°C and continue to keep it for 2h, and the heating rate is 5°C / min. The product after high-temperature carbonization is dispersed in 2M sodium hydroxide solution (solvent: alcohol water volume ratio 1:3), centrifuged at 50°C for 24h, washed with water to neutrality, and dried for standby use. Example 1 is a spherical shape with a uniform size and a cavity structure, and the shell wall presents a porous structure, the pore size distribution is mainly in the range of 2-30nm, the porosity is 29.85%, and the wall thickness is 35nm. The internal carbon core is about 296nm, forming a cavity, and its size (assuming that the kernel is in the center of the cavity surrounded by the shell wall, the distance from the kernel to the shell wall) is about 160nm.
[0100] Bromine fixation ability test: Use 30-50nm Al2O3 polishing powder to polish a 6mm diameter rotating ring disk electrode (ring is Pt, disk is glassy carbon) until the surface is smooth and traceless, rinse repeatedly with deionized water, and dry for use. Take 2.5mg of the above-prepared material, mix it with 0.4g isopropanol and 10μL 0.05wt.% Nafion solution by ultrasonic mixing to form a uniform slurry. Use a micro-injector to draw 10μL of the above slurry and transfer it to the glassy carbon electrode and evenly distribute it on the upper surface. After the solvent evaporates completely, a thin film electrode with a smooth surface is obtained as a working electrode. The bromine fixation ability test device and conditions are the same as those of Comparative Example 2, except that only the ring disk electrode after the above treatment is used as the working electrode.
[0101] Embodiment 2:
[0102] Weigh 2mmol of resorcinol and 4mmol of formaldehyde and dissolve them in 100mL of deionized water under stirring. Add 0.5mmol of 1,6-hexanediamine to the above solution, react for 30min, add 50μL of 25% ammonia water, and react at 80℃ for 4h. Cool to room temperature, centrifuge, wash the solid with water, and dry to obtain solid polymer spheres. Take 400mg of the prepared solid polymer spheres and disperse them in 100mL of deionized water, add 1.0mL of 25% ammonia water and 24mL of anhydrous ethanol, add 20mL of pre-dissolved CTAB aqueous solution (15mmol CTAB is added to 100mL of water to make an aqueous solution) after ultrasonic dispersion, stir for 30min, add 1mL of TEOS, react for 16h, centrifuge, wash the solid with deionized water until neutral, and dry for use. The resulting spheres are uniform in size with a diameter of about 500nm.
[0103] Take 2.0g of the material obtained in the previous step and lay it flat in a corundum boat, place it in a tube furnace, and perform high-temperature carbonization in Ar, first keep it at 150°C for 2h, then heat it to 700°C and continue to keep it for 2h, with a heating rate of 5°C / min. The product after high-temperature carbonization is dispersed in a 2M sodium hydroxide solution (solvent: alcohol-water volume ratio 1:3), centrifuged at 50°C for 24h, washed with water to neutrality, and dried for standby use. The prepared Example 1 is a sphere with a uniform size and a cavity structure, and the shell wall presents a porous structure with a porosity of 30.64%, a pore size distribution mainly in the range of 3-30nm, and a wall thickness of 35nm. The internal carbon core is about 290nm, forming a cavity, and its size (assuming that the core is in the center of the cavity surrounded by the shell wall, the distance from the core to the shell wall) is about 150nm.
[0104] Bromine fixation ability test: Use 30-50nm Al2O3 polishing powder to polish a 6mm diameter rotating ring disk electrode (ring is Pt, disk is glassy carbon) until the surface is smooth and traceless, rinse repeatedly with deionized water, and dry for use. Take 2.5mg of the above-prepared material, mix it with 0.4g isopropanol and 10μL 0.05wt.% Nafion solution by ultrasonic mixing to form a uniform slurry. Use a micro-injector to draw 10μL of the above slurry and transfer it to the glassy carbon electrode and evenly distribute it on the upper surface. After the solvent evaporates completely, a thin film electrode with a smooth surface is obtained as a working electrode. The bromine fixation ability test device and conditions are the same as those of Comparative Example 2, except that only the ring disk electrode after the above treatment is used as the working electrode.
[0105] Embodiment 3:
[0106] Weigh 2mmol of resorcinol and 4mmol of formaldehyde and dissolve them in 100mL of deionized water under stirring. Add 0.5mmol of 1,6-hexanediamine to the above solution, react for 30min, add 50μL of 25% ammonia water, and react at 80℃ for 4h. Cool to room temperature, centrifuge, wash the solid with water, and dry to obtain solid polymer spheres. Take 400mg of the prepared solid polymer spheres and disperse them in 100mL of deionized water, add 1.0mL of 25% ammonia water and 24mL of anhydrous ethanol, add 20mL of pre-dissolved CTAB aqueous solution (15mmol CTAB is added to 100mL water to make an aqueous solution) after ultrasonic dispersion, stir for 30min, add 1mL of TEOS, react for 20h, centrifuge, wash the solid with deionized water until neutral, and dry for use.
[0107] Take 2.0g of the material obtained in the previous step and lay it flat in a corundum boat, place it in a tube furnace, and carry out high-temperature carbonization in Ar, first keep it at 150°C for 2h, then heat it to 700°C and continue to keep it for 2h, with a heating rate of 5°C / min. The product after high-temperature carbonization is dispersed in 2M sodium hydroxide solution (solvent: alcohol water volume ratio 1:3), centrifuged at 50°C for 24h, washed with water to neutrality, and dried for standby use. The prepared Example 3 is a sphere with a uniform size and a cavity structure, and the shell wall presents a porous structure with a porosity of 31.47%, a pore size distribution mainly in the range of 3-30nm, and a wall thickness of 37nm. The internal carbon core is about 270nm, forming a cavity, and its size (assuming that the kernel is in the center of the cavity surrounded by the shell wall, the distance from the kernel to the shell wall) is about 160nm.
[0108] Embodiment 4:
[0109] Take 2mmol resorcinol and 4mmol formaldehyde and dissolve them in 100mL deionized water under stirring. Add 0.5mmol 1,6-hexanediamine to the above solution, react for 30min, add 50μL of 25% ammonia water, and react at 80℃ for 4h. Cool to room temperature, centrifuge, wash the solid with water, and dry to obtain solid polymer spheres. Take 400mg of the prepared solid polymer spheres and disperse them in 100mL deionized water. Add 1.0mL of 25% ammonia water and 24mL of anhydrous ethanol. After ultrasonic dispersion, add 10mL of pre-dissolved CTAB aqueous solution (15mmol CTAB is added to 100mL water to make an aqueous solution), stir for 30min, add 1mL TEOS, react for 16h, centrifuge, wash the solid with deionized water until neutral, and dry for use.
[0110] Take 2.0g of the material obtained in the previous step and lay it in a corundum boat, place it in a tube furnace, and carry out high-temperature carbonization in Ar, first keep it at 300°C for 2h, then heat it to 900°C and continue to keep it for 2h, and the heating rate is 5°C / min. The product after high-temperature carbonization is dispersed in 2M sodium hydroxide solution (solvent: alcohol water volume ratio 1:3), centrifuged at 50°C for 24h, washed with water to neutrality, and dried for standby use. The prepared embodiment 4 is a sphere with a uniform size and a cavity structure, and the shell wall presents a porous structure with a porosity of 31.00%, a pore size distribution mainly in the range of 3-20nm, and a wall thickness of 35nm. The internal carbon core is about 275nm, forming a cavity, and its size (assuming that the core is in the center of the cavity surrounded by the shell wall, the distance from the core to the shell wall) is about 160nm.
[0111] Bromine fixation ability test: Use 30-50nm Al2O3 polishing powder to polish a 6mm diameter rotating ring disk electrode (ring is Pt, disk is glassy carbon) until the surface is smooth and traceless, rinse repeatedly with deionized water, and dry for use. Take 2.5mg of the above-prepared material, mix it with 0.4g isopropanol and 10μL 0.05wt.% Nafion solution by ultrasonic mixing to form a uniform slurry. Use a micro-injector to absorb 10μL of the above slurry and transfer it to the glassy carbon electrode. After the solvent evaporates completely, a thin film electrode with a smooth surface is obtained as a working electrode. The bromine fixation ability test device and conditions are the same as those of Comparative Example 2, except that only the above-treated ring disk electrode is used as the working electrode.
[0112] Embodiment 5:
[0113] After thorough grinding, 0.05 g of the material prepared in Example 1 was weighed and mixed evenly with 0.2 g of 0.05 wt % Nafion solution and 3 g of isopropanol, and then sprayed on an original carbon felt with a size of 3 cm*3 cm*5 mm under ultrasonication for several hours.
[0114] Electrochemical performance test (CV): The working electrode was the carbon felt prepared as described above, and the test apparatus and conditions were the same as those in Comparative Example 8.
[0115] Self-discharge performance test: Assemble the zinc-bromine flow battery, use the carbon felt electrode prepared and treated as above for the positive electrode, and use the untreated original carbon felt electrode for the negative electrode, and other conditions are the same as those in the above comparative example 8. The side of the sprayed material faces the diaphragm;
[0116] The current density is 80 mA cm -2 , with a surface capacity of 40 mAh cm -2 The zinc deposition morphology was characterized under the following conditions: a zinc-bromine flow battery was assembled, the carbon felt electrode prepared and treated as above was used for the negative electrode, and the untreated original carbon felt electrode was used for the positive electrode. Other conditions and operations were the same as those in Comparative Example 8.
[0117] The current density is 80 mA cm-2 The battery performance test was carried out under the following conditions: a zinc-bromine flow battery was assembled, and the carbon felt electrodes prepared and treated as above were used for the positive and negative electrodes, and other conditions were the same as those in the above comparative example 8.
[0118] The current density is 180 mA cm -2 The battery long cycle performance test was carried out under the following conditions: the positive and negative electrodes used the carbon felt electrodes prepared and treated as above, and the other conditions were the same as those in the above comparative example 8.
[0119] Embodiment 6:
[0120] After thorough grinding, 0.05 g of the material prepared in Example 2 was weighed and mixed evenly with 0.2 g of 0.05 wt % Nafion solution and 3 g of isopropanol, and then sprayed on an original carbon felt with a size of 3 cm*3 cm*5 mm under ultrasonication for several hours.
[0121] Electrochemical performance test (CV): The working electrode was the carbon felt prepared as described above, and the test apparatus and conditions were the same as those in Comparative Example 8.
[0122] Self-discharge performance test: Assemble the zinc-bromine flow battery, use the carbon felt electrode prepared and treated as above for the positive electrode, and use the untreated original carbon felt electrode for the negative electrode, and other conditions are the same as those in the above comparative example 8. The side of the sprayed material faces the diaphragm;
[0123] The current density is 80 mA cm -2 , with a surface capacity of 40 mAh cm -2 The zinc deposition morphology was characterized under the following conditions: a zinc-bromine flow battery was assembled, the carbon felt electrode prepared and treated as above was used for the negative electrode, and the untreated original carbon felt electrode was used for the positive electrode. Other conditions and operations were the same as those in Comparative Example 8.
[0124] The current density is 80 mA cm -2 The battery performance test was carried out under the following conditions: a zinc-bromine flow battery was assembled, and the carbon felt electrodes prepared and treated as above were used for the positive and negative electrodes, and other conditions were the same as those in the above comparative example 8.
[0125] Embodiment 7:
[0126] After thorough grinding, 0.05 g of the material prepared in Example 3 was weighed and mixed evenly with 0.2 g of 0.05 wt % Nafion solution and 3 g of isopropanol, and then sprayed on an original carbon felt with a size of 3 cm*3 cm*5 mm under ultrasonication for several hours.
[0127] Electrochemical performance test (CV): The working electrode was the carbon felt prepared as described above, and the test apparatus and conditions were the same as those in Comparative Example 8.
[0128] Self-discharge performance test: Assemble the zinc-bromine flow battery, use the carbon felt electrode prepared and treated as above for the positive electrode, and use the untreated original carbon felt electrode for the negative electrode, and other conditions are the same as those in the above comparative example 8. The side of the sprayed material faces the diaphragm;
[0129] The current density is 80 mA cm -2 , with a surface capacity of 40 mAh cm -2 The zinc deposition morphology was characterized under the following conditions: a zinc-bromine flow battery was assembled, the carbon felt electrode prepared and treated as above was used for the negative electrode, and the untreated original carbon felt electrode was used for the positive electrode. Other conditions and operations were the same as those in Comparative Example 8.
[0130] The current density is 80 mA cm -2 The battery performance test was carried out under the following conditions: a zinc-bromine flow battery was assembled, and the carbon felt electrodes prepared and treated as above were used for the positive and negative electrodes, and other conditions were the same as those in the above comparative example 8.
[0131] Embodiment 8:
[0132] After thorough grinding, 0.05 g of the material prepared in Example 4 was weighed and mixed with 0.2 g of 0.05 wt % Nafion solution and 3 g of isopropanol, and then sprayed on an original carbon felt with a size of 3 cm*3 cm*5 mm under ultrasonication for several hours.
[0133] Electrochemical performance test (CV): The working electrode was the carbon felt prepared as described above, and the test apparatus and conditions were the same as those in Comparative Example 8.
[0134] Self-discharge performance test: Assemble the zinc-bromine flow battery, use the carbon felt electrode prepared and treated as above for the positive electrode, and use the untreated original carbon felt electrode for the negative electrode, and other conditions are the same as those in the above comparative example 8. The side of the sprayed material faces the diaphragm;
[0135] The current density is 80 mA cm -2 , with a surface capacity of 40 mAh cm -2 The zinc deposition morphology was characterized under the following conditions: a zinc-bromine flow battery was assembled, the carbon felt electrode prepared and treated as above was used for the negative electrode, and the untreated original carbon felt electrode was used for the positive electrode. Other conditions and operations were the same as those in Comparative Example 8.
[0136] The current density is 80 mA cm -2 The battery performance test was carried out under the following conditions: a zinc-bromine flow battery was assembled, and the carbon felt electrodes prepared and treated as above were used for the positive and negative electrodes, and other conditions were the same as those in the above comparative example 8.
[0137] Figure 1The SEM images of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, Comparative Example 6, Example 3, and Example 4 are shown. As shown in the figure, the size of the prepared polymer sphere is about 380nm (Comparative Example 1), and the size of the solid carbon sphere obtained by directly subjecting it to high temperature carbonization shrinks (thermal polycondensation of the polymer), about 296nm (Comparative Example 2), and the size increases to 518nm (Comparative Example 3) after the silicon dioxide layer is coated on the polymer sphere (Comparative Example 1). Due to the confined pyrolysis, the material prepared by the present invention is a spherical shape with a cavity structure of uniform size, and the shell wall presents a porous structure (Example 3, Example 4), and a significant pore size distribution is shown at about 3, 11, and 20nm, and the wall thickness is 35nm. The internal carbon core is about 296nm, forming a cavity whose size (the distance from the inner core to the shell wall) is about 160nm. However, when the surfactant CTAB is not added during the silica shell coating process (Comparative Example 4), the coating reaction time is short (Comparative Example 5), or the high-temperature carbonization has no low-temperature and high-temperature carbonization stages (Comparative Example 6), core-shell carbon nanospheres with a cavity structure cannot be obtained.
[0138] Figure 2 TEM images of Comparative Example 2, Comparative Example 4, Comparative Example 5, Comparative Example 6, Example 3, and Example 4. The polymer spheres are directly subjected to high-temperature carbonization to obtain solid carbon spheres (Comparative Example 2), and due to the confined pyrolysis, a certain gap will be generated at the interface between the confined layer coating layer and the polymer carbon along with the shrinkage of the polymer sphere particle size. The gas generated by pyrolysis will trigger the self-activation of the nano-space confinement, and the etching will occur from the outer surface of the carbon sphere, so that the cavity generated at the interface will gradually increase. At the same time, the added surfactant CTAB will decompose at a temperature higher than 300°C, and the carbon-containing material will gradually precipitate to form a silica / carbon composite shell layer. After the silica is removed by alkali solution, a porous shell wall with a thickness of about 35nm is obtained (Example 3, Example 4), and the carbon core is about 276nm, with a large cavity, and its size (the distance from the inner core to the shell wall) is about 160nm. However, when the surfactant CTAB is not added during the coating of the silica shell layer (Comparative Example 4), the coating reaction time is short (Comparative Example 5), or the high-temperature carbonization has no low-temperature and high-temperature carbonization stages (Comparative Example 6), the prepared material fails to successfully prepare the coating layer, and a thick shell wall and a regular core-shell structure cannot be obtained.
[0139] Figure 3It is a pore size distribution diagram of Comparative Example 2, Comparative Example 4, Comparative Example 5, Comparative Example 6, Example 1, Example 2, and Example 4. As can be seen from the figure, solid carbon spheres (Comparative Example 2) and non-core-shell structure carbon materials (Comparative Example 4, Comparative Example 5, Comparative Example 6) have no obvious pore size distribution, while the materials prepared by the present invention (Example 1, Example 2, Example 4) show obvious pore size distribution at about 3, 11, and 20 nm due to the etching effect of the confined pyrolysis process. And when the amount of CTAB added increases (Example 2), the pores at about 3 nm become about 2 nm. This is because the carbon species decomposed and deposited in the coating layer are more and denser, and a pore structure with a smaller pore size appears after etching the silicon dioxide layer.
[0140] Figure 4 It is a porosity comparison chart of Comparative Example 2, Comparative Example 6, Example 1, Example 2, and Example 4. As can be seen from the figure, the solid carbon sphere (Comparative Example 2) and the non-core-shell structure carbon material (Comparative Example 4, Comparative Example 5, Comparative Example 6) have extremely low porosity, about 1%, while the materials prepared by the present invention (Example 1, Example 2, Example 4) have obvious pore size distribution due to the etching effect of the confined pyrolysis process, so the porosity is as high as 30%.
[0141] Figure 5 It is a comparison chart of the specific surface areas of Comparative Example 2, Comparative Example 4, Comparative Example 5, Comparative Example 6, Example 1, Example 2, Example 3, and Example 4. Figure 3 The pore size distribution corresponds to that of solid carbon spheres (Comparative Example 2) and non-core-shell structured carbon materials (Comparative Example 4, Comparative Example 5, Comparative Example 6) due to the lack of obvious pore structure. The core-shell homogeneous carbon nanosphere materials with a cavity structure prepared by the present invention (Example 1, Example 2, Example 3, Example 4) have a significantly increased specific surface area due to the pore size in multiple ranges.
[0142] Figure 6 The cyclic voltammetry curves (CV) of Comparative Example 8, Comparative Example 9, Comparative Example 10, Comparative Example 12, Example 5, Example 6, Example 7, and Example 8 are shown. After the carbon felt is modified with the material prepared by the present invention (Example 5, Example 6, Example 7, and Example 8), the reduction peak current of bromine is significantly increased, and the electrochemical activity is significantly improved, indicating that it is beneficial to promote the reaction kinetics of the positive electrode bromine electrode pair, which is due to the strong adsorption effect of the carbon core and carbon shell, the increased specific surface area, and the increased active sites. After modifying the solid carbon sphere (Comparative Example 9) and the non-core-shell structure carbon material (Comparative Example 10 and Comparative Example 12), compared with the original carbon felt (Comparative Example 8), the catalytic activity is only slightly improved because these materials have a smaller specific surface area and fewer reactive active sites.
[0143] Figure 7It is a comparison chart of the bromine fixation ability of Comparative Example 2, Comparative Example 4, Comparative Example 6, Example 1, Example 2, and Example 4. The test was performed using a rotating ring disk electrode. First, according to Faraday's law, a part of the Br2 generated on the disk electrode is captured in the material of the disk electrode through aperture screening or adsorption, and the other part is not captured and diffuses to the ring electrode and is reduced by the reduction potential on the ring electrode. Therefore, the current value on the ring can represent the amount of uncaptured bromine. The smaller the current value, the stronger the bromine fixation ability of the material. As can be seen from the figure, compared with the original ring disk electrode (Comparative Example 13) and solid carbon spheres (Comparative Example 2), non-core-shell structured carbon materials (Comparative Example 4, Comparative Example 6), the core-shell homogeneous carbon nanosphere material with a cavity structure of the present invention (Example 1, Example 2, Example 4) greatly reduces the limiting current value, indicating that the electrode of the present invention has a carbon core, a carbon shell and a larger cavity with strong adsorption capacity to accommodate bromine, and exhibits excellent bromine fixation ability, which can inhibit the migration and diffusion of bromine and slow down the self-discharge of the battery.
[0144] Figure 8 The current density is 80 mA cm -2 Under the conditions, the self-discharge performance diagram of the zinc-bromine flow battery assembled by Comparative Example 8, Comparative Example 9, Comparative Example 10, Comparative Example 12, Example 5, Example 6, Example 7, and Example 8. It can be seen from the figure that the coulomb efficiency of the battery assembled with the original carbon felt (Comparative Example 8) can only be maintained at 42.62% after being placed for 24 hours, and the coulomb efficiency of the frontal electrode modified with solid carbon balls (Comparative Example 9) and non-core-shell structure carbon materials (Comparative Example 10, Comparative Example 12) is increased to about 50%. The battery assembled with the core-shell homogeneous carbon nanosphere material with a cavity structure prepared by the present invention (Example 5, Example 6, Example 7, Example 8) can have a coulomb efficiency of up to 75%-78%, and the self-discharge performance is significantly improved, indicating that the electrode structure of the present invention is conducive to inhibiting the migration and diffusion of bromine and slowing down the capacity loss of the battery.
[0145] Fig. 9 The zinc deposition morphology of Comparative Example 8, Comparative Example 9, Comparative Example 10, Example 5, Example 6, and Example 7. Zinc on the original carbon felt (Comparative Example 8) is directly deposited on the carbon fiber, which is easy to form dendritic and spongy zinc. In Comparative Examples 9 and 10, the carbon fiber surface is sprayed with carbon ball material, which can provide more zinc-affinity sites, making the zinc deposition relatively uniform. In Examples 5, 6, and 7, the electrode surface forms a very dense, smooth, and flat zinc deposition morphology. The core-shell homogeneous carbon nanospheres with a cavity structure have a strong affinity for zinc, and the gaps between the carbon balls and the cavity structure can preferentially accommodate more deposited zinc, making the zinc deposition more uniform and flat, and not easy to form zinc dendrites.
[0146] Fig.10 The current density is 80 mA cm-2 The battery performance diagrams of Comparative Example 8, Comparative Example 9, Comparative Example 10, Comparative Example 12, Example 5, Example 6, and Example 7 are shown. Compared with the original carbon felt (Comparative Example 8), the battery performance of the modified solid carbon sphere (Comparative Example 9) and the non-core-shell structured carbon material (Comparative Example 10 and Comparative Example 12) is only slightly improved, especially the weak bromine fixation ability makes the coulomb efficiency not significantly improved, while the core-shell homogeneous carbon nanosphere material with a cavity structure of the present invention significantly promotes the reaction kinetics of the bromine electrode pair, effectively improves the coulomb efficiency, voltage efficiency and energy efficiency of the battery (Example 5, Example 6, Example 7), especially the coulomb efficiency is as high as more than 99%, and the voltage efficiency is as high as more than 85%.
[0147] Fig.11 The current density is 180 mA cm -2 The battery performance diagram of Comparative Example 8, Comparative Example 9, Example 5, and Example 8 as both the positive electrode material and the negative electrode material of zinc-bromine flow battery. As shown in the figure, due to the larger polarization caused by the higher current density, the battery assembled with the original carbon felt (Comparative Example 8) cannot operate normally. After the battery assembled with the non-core-shell structure carbon material (Comparative Example 9) cycles for more than 200 times, the battery fails due to the loss of active substances caused by the diffusion of bromine on the positive electrode side and the problem of zinc dendrites on the negative electrode side. The core-shell homogeneous carbon nanosphere material (Example 5, Example 8) of the present invention with a cavity structure has a strong adsorption capacity and a large specific surface area, which greatly improves the catalytic activity of bromine and alleviates the problem of bromine diffusion. At the same time, when modifying the negative electrode, it can provide more sites and space for zinc deposition, which is conducive to regulating the negative electrode zinc deposition / dissolution process, and effectively alleviates the zinc dendrite problem. When it is used as the positive and negative electrode materials of zinc-bromine flow batteries, it can significantly improve the performance and cycle life of the battery (no obvious performance attenuation after 600 cycles).
Claims
1. An electrode for a zinc-bromine flow battery, characterized in that: The electrode uses a conductive current collector as a matrix, and a core-shell homogeneous carbon nanosphere material with a cavity structure is supported or attached on the matrix. The core-shell homogeneous carbon nanosphere material with a cavity structure has a carbon core and a carbon shell layer, a core size of 50-500nm, a cavity size (assuming that the core is at the center of the cavity surrounded by the shell wall, the distance from the core to the shell wall) of 40-250nm, a shell wall thickness of 5-60nm, a shell wall pore diameter of 1-60nm, and a porosity of 10%-50%.
2. The electrode according to claim 1, characterized in that: The core-shell homogeneous carbon nanosphere material with a cavity structure has an inner core size of 100-400nm, a cavity size (assuming that the inner core is at the center of the cavity surrounded by the shell wall, the distance from the inner core to the shell wall) of 50-200nm, a shell wall thickness of 10-50nm, a shell wall pore diameter of 1-50nm, and a porosity of 20%-40%.
3. The electrode according to claim 1, characterized in that: The core-shell homogeneous carbon nanosphere material with a cavity structure has a loading amount of 1-15 mg / cm 2 , the substrate is carbon felt, graphite felt or carbon cloth.
4. A method for preparing an electrode according to any one of claims 1 to 3, characterized in that: 1) Weigh resorcinol and formaldehyde and dissolve them in 100 mL of deionized water under stirring; then, add a certain amount of 1,6-hexanediamine to the above solution, react for 30-50 minutes, then add ammonia water and react for a period of time at 80-100°C. After cooling, centrifugation, washing and drying, solid polymer balls are obtained; The molar ratio of resorcinol to formaldehyde is constant at 1:2-1:4, the amount of resorcinol is 2mmol-5mmol, the amount of 1,6-hexanediamine is 0.5-1mmol, the amount of ammonia water is 50-100 μL (mass fraction 20-30%), and the reaction time is 2-6h; 2) Dispersing the solid polymer spheres in 100 mL of deionized water, adding ammonia water and anhydrous ethanol, adding a pre-dissolved hexadecyltrimethylammonium bromide (CTAB) aqueous solution after ultrasonic dispersion, stirring for 30 minutes, adding tetraethyl orthosilicate (TEOS), reacting for a certain period of time, centrifuging, washing the solid with deionized water until neutral, and drying to obtain a core-shell structure polymer @ silicon oxide material; The addition amounts of ammonia water (mass fraction 20-30%) and anhydrous ethanol are 1.0-3.0 mL and 20-30 mL, the amount of the CTAB aqueous solution is 10-50 mL (10-20 mmol CTAB is added to 100 mL water to prepare an aqueous solution), the amount of TEOS is 1-5 mL, and the reaction time is 10-20 h; 3) subjecting the core-shell structure polymer@silicon oxide material to high temperature pyrolysis and carbonization to obtain a core-shell carbon@silicon oxide material; 4) dispersing the core-shell carbon@silicon oxide material in an alkaline solution for reaction, centrifuging, washing the solid with water until it is neutral, and drying to obtain the core-shell homogeneous carbon nanosphere material with a cavity structure; 5) Loading the core-shell homogeneous carbon nanosphere material with a cavity structure on a conductive current collector matrix to obtain the electrode.
5. The preparation method according to claim 4, characterized in that: In step 3), the high-temperature pyrolysis carbonization is divided into two stages. The temperature of the first stage is 150-350°C, the time is 1-5h, and the heating rate is 1-10°C / min. The temperature of the second stage is 500-900°C, the time is 1-5h, and the heating rate is 1-10°C / min. An inert atmosphere (such as nitrogen and / or argon) is used.
6. The preparation method according to claim 4, characterized in that: In step 4), the alkaline solution used for etching silicon oxide is composed of 2-4M sodium hydroxide solution (solvent: alcohol water volume ratio 1:3-1:6), and the etching conditions are 50-80° C. for reaction for 20-36 hours.
7. The preparation method according to claim 4, characterized in that: In step 5), the core-shell homogeneous carbon nanosphere material with a cavity structure is loaded in the following manner: adding the core-shell homogeneous carbon nanosphere material with a cavity structure into isopropanol, adding a binder at the same time, and then spraying it onto a conductive current collector substrate after ultrasonic dispersion.
8. The preparation method according to claim 7, characterized in that: The binder is one of Nafion, PVDF or PTFE, and the mass ratio of the binder to the core-shell homogeneous carbon nanosphere material with a cavity structure is 2-8; the mass ratio of the isopropanol to the core-shell homogeneous carbon nanosphere material with a cavity structure is 25-100.
9. An electrode according to any one of claims 1 to 3 used as a positive electrode or a negative electrode of a zinc-bromine flow battery.
10. The preparation method according to claim 9, characterized in that: The side of the core-shell homogeneous carbon nanosphere material with a cavity structure supported or attached (by, for example, spraying) faces the separator.
Citation Information
Patent Citations
Applications of cage-like porous carbon material in flow batteries
CN107845813A
Improved electrode for redox flow battery
CN108352507A
Carbon-based electrocatalyst, catalyst-supported electrode and preparation and application of carbon-based electrocatalyst and catalyst-supported electrode
CN115719815A
Porous electrode base material and method for producing the same
JP2016173966A